Ovid and the myth of the Argonauts - Wesołowska, Elżbieta (Balcanica Posnaniensia. Acta et studia, 1990)
The article analyzes the problem of the presence and function of the Argonaut myth in the works of Ovid. The problem is significant for studies on the reception of Greek mythology in Roman literature and on the ways of its reinterpretation. The aim of the work is to show how the poet uses the motif of Jason’s expedition and the figure of Medea in different literary genres. The author applies philological and comparative analysis of Ovid’s texts, especially the Metamorphoses, the Heroides, and the lost tragedy Medea. The most important results indicate that Ovid does not present the myth uniformly, but develops its various threads depending on the generic context – from brief allusions to extensive narratives. A particularly important role is played by the figure of Medea, presented as a psychologically complex heroine in whom love, passion, and magic intertwine. The analysis also demonstrates a strong emphasis on the magical element and an interest in female psychology, which is characteristic of Ovid’s work. The conclusion is that the Argonaut myth serves in the poet’s work as a universal literary motif allowing exploration of themes of love, betrayal, and transformation.